Solvent effects on the crystallization and structure of ternary copper(ii) coordination compounds with l-threonine and 1,10-phenanthroline - Darko Vušak; Katarina Ležaić; Jurica Jurec; Dijana Žilić; Biserka Prugovečki (Heliyon, 2022)
Solution-based and solid-state reactions of copper(ii) compounds, 1,10-phenanthroline and l-threonine were investigated. Eight new ternary coordination compounds were obtained:[Cu(l-Thr)(H2O)(phen)]2SO4∙10H2O (1a∙10H2O), [Cu(l-Thr)(H2O) (phen)]2SO4∙4.3H2O (1a∙4.3H2O), {[Cu(μ-l-Thr)(phen)]2SO4∙3.5H2O}n (1b∙3.5H2O), [Cu(l-Thr)(H2O)(phen)][Cu(l-Thr)(CH3OH)(phen)]SO4∙2H2O∙CH3OH (1c∙2H2O∙CH3OH), [Cu(l-Thr)(H2O)(phen)][Cu(l-Thr)(CH3OH)(phen)]SO4∙4H2O (1c∙4H2O), [Cu(l-Thr)(CH3OH)(phen)]2SO4∙H2O (1d∙H2O), [Cu(l-Thr)(H2O)(phen)][Cu(l-Thr)(CH3OH)(phen)][Cu(SO4)(l-Thr)(phen)]HSO4∙H2O∙3CH3OH (1e·H2O·3CH3OH), [Cu(l-Thr)(H2O)(phen)][Cu(l-Thr)(phen)(py)]SO4 (1f) (phen = 1,10-phenanthroline, l-Thr = l-threoninate, py = pyridine). X-ray crystal structure analysis of the prepared ternary coordination compounds revealed extensive hydrogen bonding and π-interactions that link complex species, anions and solvent molecules into 3D architectures. The water/methanol solvent molecules are found in pockets and/or channels in seven solvates. ESR spectra of different types of compounds were also investigated. In all measured compounds the unpaired electron of the copper(II) ion is located in the dx2-y2 orbital which is in agreement with elongated square-pyramidal geometry. Compound 1a∙10H2O showed substantial cytotoxic activity toward human hepatocellular carcinoma (HepG2) and acute monocytic leukaemia (THP-1) cell lines.